P-OGC40 Enhanced recovery after oesophagectomy at Oxford University Hospitals: the benefit of having a discharge target. (16th December 2021) - Menon, Nainaka; Antonowicz, Stefan; Matarangelo, Antonio; Ash, Stephen; Owen, Richard; Ferraro, Daniele; Ghafoor, Hamira; Gillies, Richard; Marshall, Robert; Sgromo, Bruno; Maynard, Nick
Abstract: Background: Enhanced recovery after surgery (ERAS) is a multimodal approach to decreasing morbidity and accelerating return-of-function after major surgery. However, the majority of patients undergoing oesophagectomy for cancer experience some kind of complication, which extends their admission and causes pathway deviation. Thus, the value of having a discharge target (Day 8 at our institution) could be challenged. In this study we reviewed our experience using this pathway, with a focus on: (i) whether length of stay and morbidity has improved since pathway implementation (ii) describing the medical and non-medical reasons for extended admission (iii) identifying pre-operative predictors of pathway deviation. Methods: A retrospective review of a prospectively maintained database was performed. Complications are recorded during routine clinical care using standardised definitions set out by the Esophageal Complications Consensus group, and are updated in the database at a weekly departmental meeting. Median and interquartile range were used for descriptors and differences tested with Mann-Whitney U test or Chi squared tests, using SPSS ver 26. Multivariable models were fitted to establish independent predictors of pathway deviation, using a binary logistic regression approach with bootstrapping. Results: 150 of 448 patients met the 8-day target. Patients treated since 2018 were significantly more likely meet their discharge date (OR 1.28, P = 0.041) compared to 2015-2017, and have less complications. Surgical quality was unchanged. Thirty-day mortality increased but was still low (0.9% vs 1.8%, P = 0.067). Aside from having a complication (OR 4.15, P < 0.001), independent predictor of delayed discharge was female sex (OR 2.6, P = 0.003), squamous cell cancer histology (OR 2.8, P = 0.014) and low socio-economic status (OR 1.33, P = 0.014), but not age, smoking, BMI, co-morbidities and other baseline variables. Conclusions: Enhanced recovery after oesophagectomy provides clear goals for the patient and multi-disciplinary team, however the target is often not met owing to the frequent nature of post-operative complications. Nonetheless these targets provide a culture for accelerated recovery, with steady improvement in short-term outcomes over time. A number of specific patient-groups are more likely to have extended admissions independent of complications, which has implications for optimising prehabilitation services. Overall, these findings suggest that having a discharge target is valuable, even though it often is not met.